(untitled) (Scottish Historical and Archaeological Internet Reports, 2007)
This section comprised a detailed archaeological description of the excavated features of the Iron Age settlement. Features include enclosing works (inner and outer enclosures), a variety of building types (post-ring, ring-groove, ring-ditch and rectangular structures), pit graves, fence lines, pitted boundaries, fence-lines, pits, postholes and a dog burial. Radiocarbon dates are also incorporated.